Ozempic (semaglutide) - review of pharmacological properties, mechanism of action and clinical applications - Koman, Anna Maria; Przygodzka, Sabina; Gadżała, Katarzyna; Janik, Izabela; Pliszka, Marzena; Palacz, Karolina Alicja; Kułak, Klaudia Brygida; Sztybór, Izabela; Kuśmierska, Martyna; Chamera-Cyrek, Katarzyna (Quality in Sport, 2024)
Introduction: Ozempic is a new generation antihyperglycemic drug used to treat type 2 diabetes in adults whose underlying disease is not sufficiently controlled with physical activity and diet, as well as for long-term weight control in people with excess body weight and comorbidities. The aim of this study is to explore and integrate the latest literature on the analysis of the pharmacology, mechanism of action and clinical applications of Ozempic. Material and Methods of Research: A literature review focused on keywords related to the topic was performed using databases such as PubMed and Google Scholar. Results: Ozempic effectively lowers blood glucose levels and supports weight loss in patients with type 2 diabetes and obesity. Clinical trials have demonstrated its superiority over other antidiabetic medications, with significant reductions in HbA1c and body weight. Patients receiving Ozempic experienced improved glycemic control and cardiovascular outcomes, with manageable side effects. Ongoing research suggests additional benefits in cardiovascular prevention and obesity management. Conclusion: Ozempic (semaglutide) is a potent GLP-1 receptor agonist that effectively improves glycemic control and aids in weight reduction for patients with type 2 diabetes and obesity. Its practical administration, patient education, and regular monitoring are essential for optimal outcomes. Ongoing research and technological advancements, including the development of oral forms, promise to expand its applications and improve patient adherence, making Ozempic a versatile and valuable therapeutic option.